The effects of sodium bicarbonate supplementation on sprint interval swimming performance in trained competitive swimmers - Gough, L.; Price, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The use of sodium bicarbonate (NaHCO3) supplementation to improve repeated high intensity performance is recommended, however most swimming performance studies examine time trial efforts rather than repeated swims indicative of training sessions. The aim of this study therefore was to investigate the effects of sodium bicarbonate supplementation on sprint interval swimming reflective of a typical training session.